Radiological characterization of water of rivers and lakes in the Mounana region in South-Eastern Gabon - Sylvere Yannick Loemba Mouandza; Philippe Ondo Meye; Wilfried Ndong; Beaud Conrad Mabika Ndjembidouma; Evaldie-Dominique Durastanti-Rabenga Mombo; Thierry Blanchard Ekogo; Germain Hubert Ben-Bolie (Radiation Protection and Environment)
The aim of this study, which is one of the few studies undertaken in this region in Gabon, was to determine the radioactivity levels in various lakes and rivers in the Mounana region by measuring the activity concentrations of alpha- and beta-emitter radionuclides. For this purpose, gross alpha (α)-beta (β) counting was carried out using a Canberra Tenelec Gas flow counter detector. From the samples collected, about 18% and 36% contained higher grossα-activity and higher grossβ-activity compared to the World Health Organization (WHO) guideline limits of 0.5 Bq l−1and 1 Bq l−1, respectively. It was also observed that 18% of the samples collected contained both gross α-and β-activities higher than the WHO guideline limits. The gross α-activity concentrations measured ranged between 0.026 ± 0.003 Bq l−1 and 1.602 ± 0.012 Bq l−1 while the gross β-activity concentrations measured ranged between 0.15 ± 0.01 Bq l−1 and 3.00 ± 0.04 Bq l−1. Given that these waters are used by the population living in Mounana for the domestic purposes, a few may be exposed to the low levels of internal radiation but below the permissible levels of 1 mSv per annum.